Studies on Witches Broom of Moth Bean - Rathore, G S; Majumdar, V L; Champawat, R S (Annals of Arid Zone, 2016)
Yield of moth bean (Vigna aconitifolia) reduced by 88.75% at 100% to that at zero per cent disease severity. Per cent loss in yield plant-l increased progressively with increasing disease severity. Plant growth parameters of diseased plants were significantly reduced as compared to healthy plants. Spray of 250 ppm tetracycline hydrochloride suppressed the symplOmsof mycoplasma and increased the growth of plant. Seventy one varieties were screened against mycoplasmal whiches broom out of which only 25 were found to he completely resistant.